Digit mechanics in relation to endpoint compliance during precision pinch. Issue 4 (26th February 2015) - Nataraj, Raviraj; Audu, Musa L.; Li, Zong-Ming
Abstract This study investigates the mechanics of the thumb and index finger in relation to compliant endpoint forces during precision pinch. The objective was to gain insight into how individuals modulate motor output at the digit endpoints and joints according to compliance-related sensory feedback across the digits. Thirteen able-bodied subjects performed precision pinch upon elastic resistance bands of a customized apparatus instrumented with six degree-of-freedom load-cells. Compliance levels were discretely adjusted according to the number of bands connected. Subjects were provided visual feedback to control the rate of force application. Fifteen repetitions of low-to-moderate force (<20 N) pinches were analyzed at each of five compliance levels, during which force and motion data were collected. Joint angles and moments normalized by pinch force magnitude were computed. Second-order polynomials were used to characterize joint mechanics as a function of compliance. The joint degrees-of-freedom (DOFs) at the finger showed greater dependence on compliance for angular position while the thumb joint DOFs demonstrated greater dependence for normalized joint moment. The digits also adjusted coordination of their endpoint forces according to compliance. Overall, the finger may be altering its position to increase load to the joints of the thumb with changing compliance. These findings describe naturally emergent changes in digit mechanics for compliant precision pinch, which involves motor execution in response to endpoint sensory feedback. Identifying and understanding these motor patterns may provide theoretical basis for restoring and rehabilitating sensorimotor pathologies of the hand.